Pengembangan Media Pembelajaran Audio Visual Menggunakan Aplikasi Kinemaster pada Pokok Bahasan Ibadah Haji dan Umrah Kelas IX di SMP N 5 Bukittinggi - Nora Nora; Darul Ilmi; Wedra Aprison; Arifmiboy Arifmiboy (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research is motivated by several problems that the author found at SMP N 5 Bukittinggi, especially in Islamic religious education subjects in class IX where in learning, educators are still minimal in utilizing learning media, the learning media used still uses powerpoint media and lecture methods, so that in the learning process students feel bored, bored and not enthusiastic about learning. To attract students’ interest, teachers must be more creative in using learning media. This research aims to develop audio visual learning media using the Kinemaster application on the subject of the hajj and Umrah pilgrimages that is valid, practical and effective. This research is development research which has 4 stages, namely the definition stage, design stage, development stage, and dissemination stage. The results of this research are that audio visual learning media using the kinemaster application received a final validation score of 0.84 in the valid category, the practicality score obtained by the teacher was 95 in the very practical category, the practicalitu score by students was 86 obtained in the very practical category, and the effectiveness score was 0.74 obtained in the very practical category effective.